Emergence from chaos to order - Holland, John H. (John Henry) 1929-2015 (New York Basic Books, 1998)
Holland, "explores emergence--the surprisingly simple notion (the whole is more than the sum of its parts) with enormous inplications fro science, business, and the arts."
1. Before We Proceed -- 2. Games and Numbers -- 3. Maps, Game Theory, and Computer-Based Modeling -- 4. Checkers -- 5. Neural Nets -- 6. Toward a General Setting -- 7. Constrained Generating Procedures -- 8. Samuel's Checkersplayer and Other Models as Cgp's -- 9. Variation -- 10. Levels of Description and Reduction -- 11. Metaphor and Innovation -- 12. Closing.
Includes bibliographical references (pages 249-251) and index.
Keywords: Mathematical models; Game theory; Artificial intelligence